Factors associated with high-frequency illicit methadone use among rural Appalachian drug users. (July 2013) - Hall, Martin T.; Leukefeld, Carl G.; Havens, Jennifer R.
Abstract Background: In recent years there has been a sharp increase in the use of illicit methadone as well as methadone-related overdose deaths. Objective: The purpose of this study was to describe factors associated with low- and high-frequency methadone use in a cohort of rural Appalachian drug users. Methods: Interviews assessing sociodemographics, illicit drug use and drug treatment, psychiatric disorders, health and sociometric drug network characteristics were conducted with 503 rural drug users between 2008 and 2010. A two-level mixed effects regression model was utilized to differentiate low- (one use per month or less in the past six months) versus high-frequency (daily or weekly use in the past six months) illicit methadone users. Results: The lifetime prevalence of illicit methadone use in this population was 94.7% (n = 476) and slightly less than half (46.3%) were high-frequency users. In the mixed effects regression model, initiating illicit methadone use at a younger age was associated with high-frequency illicit methadone use. Taking a prescribed medication for a physical problem, undergoing additional weeks of outpatient drug free treatment, daily OxyContin® use in the past month, and having fewer ties and second-order connections in the drug network reduced the odds of high-frequency illicit methadone use. Conclusions: Rates of illicit methadone use and high-frequency illicit methadone use among this sample of rural drug users were considerably higher than those previously reported in the literature. Health practitioners in rural areas should routinely screen for illicit opioid use, including methadone.